The Utility of Euroflow MRD Assessment in Real-World Multiple Myeloma Practice - Turner, Rose; Kalff, Anna; Bergin, Krystal; Gorniak, Malgorzata; Fleming, Shaun; Spencer, Andrew (Frontiers in Oncology, 2022)
Measurable residual disease (MRD) is being recognised as an optimal method for assessing depth of response, identifying higher risk of relapse, and guiding response-based treatment paradigms for multiple myeloma (MM). Although MRD negativity is increasingly replacing complete response as the surrogate endpoint in clinical trials, its role in real-world practice is less established. We retrospectively analyzed EuroFlow MRD results from patients with newly diagnosed MM (NDMM) who underwent bortezomib, cyclophosphamide and dexamethasone (VCD) induction and high dose melphalan conditioned autologous stem cell transplant (ASCT) at the Alfred Hospital between January 2016 and December 2020. Next generation flow MRD evaluation was performed 3 months following ASCT using the standardised EuroFlow platform. 112 patients with available MRD data were identified to have received VCD induction followed by ASCT. Post ASCT MRD was undetectable in 28.6% of patients. Those who achieved MRD negativity had significantly longer progression free survival (PFS) than those with persisting MRD (24-month PFS of 85% [95% CI: 72.4-99.9%] vs 63% [95% CI: 52.9-75.3%], p = 0.022). Maintenance therapy was associated with improved PFS regardless of MRD status (24-month PFS of 100% [95% CI: NA, p = 0.02] vs 73% [95% CI: 53.1-99.6%] in MRD negative, and 75% [95% CI: 64.2-88.6%] vs 36% [95% CI: 20.9-63.2%, p = 0.00015] in MRD positive patients). Results from this retrospective study of real-world practice demonstrate that Euroflow MRD analysis following standard VCD induction and ASCT in NDMM is feasible and allows more accurate prognostication, providing a platform for response adaptive therapies.